Musafahah Method Transformation on Learning Qiraat Sab'ah in PPTQ Al-Hasan Ponorogo - Yahuda, Robbin Dayyan; Susanto, Roni; Widodo, Wahyu; Kolis, Nur; Abdillah, Bagas (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study discusses the musafahah method transformation in learning qiraat sab’ah at PPTQ Al-Hasan, Ponorogo. Using a qualitative approach, this study compares and discusses changes in the structure of the musafahah method phase A and phase B, in learning qiraat sab’ah at PPTQ al-Hasan, Ponorogo. Data was collected through interviews with 10 informants, classified as 1 kiai, 4 ustadz, and 5 students, and using the semi-structured interview method, followed by observation and documentation. Data analysis uses the Foucaultian Discursive Analysis (FDA) method. The results showed that: First, the phase A musafahah method at PPTQ al-Hasan Ponorogo was oriented to the authenticity and credibility of the qiraat sab’ah reading. Second, the phase B musafahah method at PPTQ al-Hasan Ponorogo is oriented to practical and populist aspects. Third, the results of the discursive analysis between the phase A and phase B musafahah methods at PPTQ al-Hasan Ponorogo showed that the phase B musafahah method was more relevant to be applied to actual situations and conditions because it was able to preserve and ground the qiraat sab’ah among students, as evidenced by the percentage of the number of qiraat sab’ah students which increased dramatically from 4 people to 35 people.